STRATEGI PENGAJARAN BAHASA ASING DALAM KONTEKS MULTIKULTURAL: PENDEKATAN INOVATIF DAN TANTANGANNYA - Kuntariati, Utik; Paramitha, Putu Dian Yuliani; Rinayanthi, Ni Made (Stilistika : Jurnal Pendidikan Bahasa dan Seni, 2024)
Multicultural Education in Language has become an increasingly relevant research subject in addressing the challenges of cultural diversity in educational contexts. This study aims to explore strategies for teaching foreign languages in multicultural environments with innovative approaches while highlighting potential obstacles and alternative solutions. A descriptive qualitative approach was employed to gather data through literature review, classroom observations, and interviews with educators. The research findings indicate that multicultural education in language has the potential to broaden students' cross-cultural understanding, enhance intercultural communication skills, and foster attitudes of tolerance and appreciation for diversity. Thus, this study provides valuable insights for educational practitioners in developing inclusive and responsive teaching strategies for foreign languages in multicultural settings. In multicultural environments, multicultural education in language holds great potential for expanding students' cross-cultural understanding,